2011
DOI: 10.1001/archinternmed.2010.501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiac Rehabilitation Referral Strategies on Utilization Rates

Abstract: Automatic referral combined with a patient discussion can achieve among the highest rates of CR referral reported. Wider adoption of such strategies could ensure that 45% more patients being treated for cardiac disease would have access to and realize the benefits of CR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 29 publications
4
157
0
5
Order By: Relevance
“…The lack of cardiac rehabilitation can be attributed to physician indifference, lack of instruction about referral of the patients to specialized centers, and lack of motivation (3,4,8,15). In the United States, Australia, and Great Britain, in order to improve referral rates, medical personnel are attempting to implement automated patient referral mechanisms (8,17,19,22,23). Physician awareness of CPR in our study was similar to the results obtained in the USA and Europe.…”
Section: Discussionsupporting
confidence: 69%
“…The lack of cardiac rehabilitation can be attributed to physician indifference, lack of instruction about referral of the patients to specialized centers, and lack of motivation (3,4,8,15). In the United States, Australia, and Great Britain, in order to improve referral rates, medical personnel are attempting to implement automated patient referral mechanisms (8,17,19,22,23). Physician awareness of CPR in our study was similar to the results obtained in the USA and Europe.…”
Section: Discussionsupporting
confidence: 69%
“…18 -20 Our results differed from some previous studies that showed a much higher enrollment rate in CR. 21,22 Some important limitations of these studies were that they were retrospective review of medical records from a single center with population primarily composed of non-Hispanic whites with relatively high educational levels, thus limiting generalizability 21 ; or were comparative effectiveness analysis of CR referral strategies demonstrating enrollment rate of 44% to 74%. 22 Our study suggests that although the recently established performance measure of CR referral after AMI may improve referral rates, there are still likely to be substantial gender and socioeconomic disparities in CR use that will require additional interventions to overcome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not collect data on the specific CR referral steps used at each site. It seems that the combined approach of systematic (ie, use of discharge order sets) plus liaison (personal bedside provision of information and invitation to enroll) appears to offer promise, 22 although a recent comprehensive review demonstrates that the evidence for any specific referral strategy is lacking. 6 Future studies are needed to assess the effect of comprehensive strategies on CR enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…[334][335][336] In a randomized trial of 2635 patients with CAD admitted to 11 different hospitals, a referral process that consisted of a combination of CR liaisons and an automated referral system resulted in 85.8% of patients being referred to CR and 73.5% being enrolled in CR compared with 32.2% and 29.0%, respectively, in the control group. 337 In addition, strategies such as educational interventions 335 and early appointments and start dates [338][339][340] have been shown to improve CR referral and use patterns. However, as new referral strategies become adopted into clinical practice, it will be important for clinicians to remain active in the referral process because physician advocacy remains a strong factor in determining whether patients will enroll in CR programs.…”
Section: Cardiac Rehabilitationmentioning
confidence: 99%